Rethinking Same-Sex Marriage in the Global South: A Postcolonial Critique of Human Rights Universalism - Tohari, Ilham; Zulkarnain, Muhammad Sulthon (Peradaban Journal of Law and Society, 2025)
This article explores the influence of global political will on the legalization of same-sex marriage in Third World countries, using a postcolonial and decolonial theoretical framework. By engaging with the critical perspectives of Talal Asad and Frantz Fanon, it examines how international human rights norms—particularly those framed by the Universal Declaration of Human Rights (UDHR)—are often promoted as universal values rooted in Western liberal-secular traditions. The article argues that such norms, when imposed without sensitivity to local histories, cultures, and legal traditions, risk reproducing colonial patterns of epistemic domination. Asad critiques secularism as a hegemonic discourse that erases religious and communal legal frameworks, while Fanon identifies the persistence of colonial power through normative violence embedded in global law. The article calls for a dialogical and pluralistic approach to the globalization of human rights—one that respects normative sovereignty, acknowledges epistemic diversity, and avoids reducing justice to legal conformity with Western models.